2006
DOI: 10.1051/0004-6361:20054203
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of narrow line emission and X-ray luminosity in active galactic nuclei

Abstract: Aims. We combine emission line and X-ray luminosities for 45 sources from the Chandra Deep Field South (CDF-S), and seven HELLAS sources, to obtain a new sample of 52 X-ray selected type-II active galactic nuclei (AGNs). Eighteen of our sources are very luminous with a typical, absorption-corrected 2-10 keV luminosity of f ew × 10 44 erg s −1 (type-II QSOs). Methods. We compare the emission line properties of the new sources with emission line and X-ray luminosities of known low redshift, mostly lower luminosi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
146
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(166 citation statements)
references
References 46 publications
(90 reference statements)
18
146
2
Order By: Relevance
“…10 we also plot the results from Best et al (2005) corresponding to AGN with L([OIII]) luminosity larger than 10 8.0 and 10 8.5 L , as labeled. Using the relation between the observed L(OIII) and the X-ray luminosity given by Netzer et al (2006, Eq. (1)), these L([OIII]) luminosities represent a fiducial range for local objects with X-ray luminosities similar to those in our sample (L X > 10 43 erg s −1 ) when an average extinction E(B−V) = 0.4 ± 0.2 is taken into account (see discussion in Netzer et al 2006).…”
Section: Agn Fractionsupporting
confidence: 71%
“…10 we also plot the results from Best et al (2005) corresponding to AGN with L([OIII]) luminosity larger than 10 8.0 and 10 8.5 L , as labeled. Using the relation between the observed L(OIII) and the X-ray luminosity given by Netzer et al (2006, Eq. (1)), these L([OIII]) luminosities represent a fiducial range for local objects with X-ray luminosities similar to those in our sample (L X > 10 43 erg s −1 ) when an average extinction E(B−V) = 0.4 ± 0.2 is taken into account (see discussion in Netzer et al 2006).…”
Section: Agn Fractionsupporting
confidence: 71%
“…Moreover, if line extinction is stronger in type 2 than in type 1 sources, then the type 2 quasar fraction would also be underestimated. Several independent measurements have suggested that this is indeed the case (Netzer et al 2006, and references therein). Reddening estimates from Balmer decrements suggest that the narrow-line regions of type 2 sources are more heavily reddened than those of type 1 sources (De Zotti & Gaskell 1985;Dahari & De Robertis 1988).…”
Section: Reddening and Extinctionmentioning
confidence: 86%
“…Recent IR observations strongly indicate that the narrow-line regions of type 2 quasars are significantly more obscured than those of type 1 quasars, by up to a factor of 10 (Haas et al 2005). Netzer et al (2006) suggest that [O iii]5007 luminosity is a factor of ∼2 larger in type 1 than in type 2 quasars for the same 2 -10 keV X-ray luminosity, as would be the case if type 2 sources are more reddened than type 1 sources. Finally, such a trend is also hinted at by our analysis of radio properties of type 1 and type 2 sources (Section 5.3).…”
Section: Reddening and Extinctionmentioning
confidence: 98%
“…One such possibility is the commonly used [O iii](λ5007 Å) luminosity, although some degree of anisotropy has been reported (e.g. Netzer et al 2006). In Fig.…”
Section: Mid-ir Continuum Emission and Its Relation To Agn Luminositymentioning
confidence: 99%